Democratization of Knowledge: Vernacular Education Planning in the Indian Context. Issue 1 (March 2017) - Singh, Rajarshi
This article explores the challenges of elementary education in India in view of its linguistic-cultural heterogeneity. The historical context leading to mother tongue as the ideal medium of instruction is presented, followed by a discussion on why a large number of mother tongues still remain outside the school system creating problems for the "No Child Left Behind" policy. The paradox faced by a heterogenous country that also needs language standardization or homogenization is raised to highlight the mismatch between school and home languages. Sapir-Whorf's linguistic relativity hypothesis and Paulo Freire's critical pedagogy framework are discussed to outline a model of present and alternate education pathways of Universal Primary Education.